Ignition sensitivity of solid fuel mixtures. (1st July 2018) - Fernandez-Anez, Nieves; Slatter, David J.F.; Saeed, Muhammad Azam; Phylaktou, Herodotos N.; Andrews, Gordon E.; Garcia-Torrent, Javier
Highlights: Ignition sensitivity parameters of solid fuels mixtures are reported. Ignition sensitivity depends on the way of distribution of the samples. Measured parameters are in the range of the former materials. Calculated values provides more relaxed values than the experimentally obtained for dust mixtures. Abstract: Due to both environmental concerns and the depletion of the reserves of fossil fuels, alternative and more environmentally friendly fuels, such as biomass and waste products, are being considered for partial or full fossil fuel replacement. The main disadvantage of these products is their lower energy density compared to fossil fuels. To deal with this several heat and power generation facilities are co-firing fuel mixtures. These processes involve mixtures of flammable dusts whose ignitability and explosibility characteristics are not known and therefore present un-quantified safety risk to the new technologies. This study reports on these risks and on the reactivity characteristics of two and three components dust mixtures of coal/sewage-sludge/torrefied-wood-pellet. In particular chemical composition, ignition sensitivity parameters (including minimum ignition energy, minimum ignition temperature on a layer, minimum explosive concentration) and flame speed have been determined. In all cases the measured parameters for the mixtures were within the range defined by the lower and upper value of the constituent. However, the expected values do not agree with the experimentally obtained ones, providing more relaxed values than the ones needed on this facilities.